Pengaruh Citra Merek, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Laptop Asus (Studi Kasus Pada Konsumen Laptop Asus di Kota Surabaya) (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Competition in the laptop industry today is getting tougher. Each of these laptop manufacturers creates laptop products that have good quality, to be able to have a competitive advantage in the laptop industry. This study aims to explain the influence of brand image, price, and product quality in influencing purchasing decisions from ASUS brand laptops and which ones have the greatest influence on purchasing decisions on ASUS brand laptops. Brand image is a requirement of a strong brand. So if the manufacturer creates a brand image, that image will be difficult to erase from the memory of consumers. In creating a brand image, manufacturers must slowly and carefully so that the brand image they create can attract and make consumers always remember the brand.